The Quranic Encouragement to Seek Knowledge and its Impact on Guiding the Individual Towards Understanding (Al-Farooq Journal of Sciences, 2026)
The research aimed to analyze the Quranic verses that encourage the pursuit of knowledge to extract their inherent educational and cognitive significance, clarify the Quranic concept of knowledge and its impact on shaping the consciousness of the Muslim individual, and examine the extent to which this Quranic encouragement is reflected in the behavior of the contemporary individual while identifying the factors influencing it. The researcher used the deductive and descriptive-analytical method to analyze texts and derive their meanings, as well as the partial inductive method to track verses and link them to reality. The research utilized tools including the textual analysis of the Holy Quran in light of authoritative interpretations, referencing educational and scientific sources, and monitoring manifestations of contemporary cognitive behavior in comparison with Quranic content.The research concluded that Quranic encouragement constitutes an integrated educational system that establishes knowledge as a spiritual and civilizational necessity for achieving vicegerency (Istikhlaf) on Earth. It also established ethical constraints linking knowledge with piety (Taqwa) and reverence to direct it toward the public good. Furthermore, it revealed that this encouragement enhances intrinsic motivation by transforming the pursuit of knowledge into an act of worship that combines sensory perception with intellectual insight, necessitating the integration of these values into contemporary educational systems. The research recommended the redesign of educational curricula to integrate the values of Quranic encouragement into various scientific disciplines, and the adoption of teaching strategies based on inquiry and reflection. It also emphasized designing guidance programs that utilize Quranic stories to build a scientific personality, supporting interdisciplinary studies that bridge Sharia and applied sciences, and the necessity of training teachers in value-based guidance competencies to serve as role models who combine cognitive mastery with moral excellence.